Sensitivity Analysis Method for Traffic Impact of Projects on Transport Network Based on BP Neural Network - Ren Qiliang (2008 International Conference on Information Management, Innovation Management and Industrial Engineering, 2008)
There is no theoretical basis about resolving scheme for traffic impact of large scale projects because of the absence of the sensitive analysis method. The sensitive analysis index system of traffic impact, the computing model and the BP neural network model about the sensitive analysis are built. To prove the application of the method, Chongqing NanAn sports center is given as an example, the main sensitive index and its range of the sports center were found.